PERSEPSI SERVANT LEADERSHIP PERGURUAN TINGGI DI KOTA PALU - Adda, Harnida (Fakultas Ekonomi Universitas Tadulako, 2018)
Leadership gives its own color in organizational management. Leadership style that suits the character of the organization will contribute in the effectiveness of decision making and policy making. The college as Center of Excellent is required to be able for answer the challenges of environmental change with creating graduates who have qualities that match the demand of the labor market. Servant leadership leadership style is seen as one of the leadership styles that are able to fulfill that goal. Therefore, this study is intended to analyze the character servant leadership that is owned by the ranks of university leaders. This research was conducted by survey method to several public and private universities in Palu City to see the implications of leadership perception. The results of this study indicate that the leadership of several universities in Palu City has servant leadership character on various aspects such as trying to build relationships, maintaining group cohesiveness, and appreciating spiritual development, self-introspection, appreciating the development of professionalism, listening to others, individual persuasion, persuasive approach, striving for vision, prioritizing problem solving, believing in institutions to improve living standards, believing that members have intrinsic value, and generally being able to understand the needs of others, but in particular leaders have not fully understood the specific needs every member of the organization in the college he leads